2012
DOI: 10.1021/la300864n
|View full text |Cite
|
Sign up to set email alerts
|

l- and d-Proline Adsorption by Chiral Ordered Mesoporous Silica

Abstract: Chiral ordered mesoporous silica (COMS) was synthesized in the presence of amino acid proline by combining tetraethyl orthosilicate and quaternized aminosilane silica sources. The as-prepared materials were activated by calcination or microwave chemical extraction to remove the organic templates. The powder X-ray diffraction and N2 adsorption characterization revealed in COMS the structural and textural features of MCM-41-type silica. The chirality of the material was disclosed by mixed and separate l- and d-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The adsorption behavior of amino acids on the surfaces of materials such as hydroxyapatite, zirconium phosphate modified silica, silica-gels, activated carbon and zeolite has been investigated. [10][11][12][13][14][15][16] Although many cases of successful immobilization using inorganic porous materials have been reported, most of the research published only uses standard activity assays to monitor the catalytic performance. In other words, the application of amino acids adsorbed on inorganic supports in terms of catalytic purposes has received very little attention.…”
Section: -8mentioning
confidence: 99%
“…The adsorption behavior of amino acids on the surfaces of materials such as hydroxyapatite, zirconium phosphate modified silica, silica-gels, activated carbon and zeolite has been investigated. [10][11][12][13][14][15][16] Although many cases of successful immobilization using inorganic porous materials have been reported, most of the research published only uses standard activity assays to monitor the catalytic performance. In other words, the application of amino acids adsorbed on inorganic supports in terms of catalytic purposes has received very little attention.…”
Section: -8mentioning
confidence: 99%
“…As proved by circular dichroism (CD) spectroscopy, monodispersed CMS spheres with chiral pores showed the asymmetric preferential adsorption of alanine with a chiral selectivity factor of 3.15 [ 74 ]. Interestingly, it was found that the adsorption of d -proline by CMS synthesized with d -proline was higher than that of l -proline, while the adsorption of l -proline by CMS synthesized with l -proline was significantly higher than that of d -proline [ 75 ]. This adsorption difference could be ascribed to the imprinting left by the amino acid during the preparation process.…”
Section: Applications Of Chiral Mesoporous Silicamentioning
confidence: 99%
“…The synthesis of chiral mesoporous silica which contains hexagonally ordered chiral channels transcribed from the organic SDA was first reported by Che et al (25). Chiral ordered mesoporous silica was synthesized in the presence of the amino acid proline (26). Pure right-and left-handed chiral mesoporous silica and organosilica phases were produced using a chiral anionic surfactant in the presence of a chiral amino acid (L-or D-arginine) (27).…”
Section: Porous Functional Silica Structures and Their Synthesismentioning
confidence: 99%